PENGARUH UKURAN DAN CASH CONVERSION CYCLE TERHADAP PROFITABILITAS PERUSAHAAN - Beby Rama Telly; Muslim Ansori (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study aims to analyze the effect of firm size and Cash Conversion Cycle on profitability at manufacturing companies listed on the Indonesia Stock Exchange which publishes financial statements for 2013-2015. Company size and Cash Conversion Cycle become independent variable, while the dependent variable is profitability measured by ROA (Return On Asset) Sugiono (2009). Hypothesis proposed in this research is company size influence to profitability and Cash Corversion Cycle influence to profitability. This research data is obtained from company financial statements taken from Indonesia Stock Exchange. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange during the year 2013 - 2015. Determination of samples using purposive sampling method and samples obtained as many as 261 companies. The hypothesis in this study was tested using multiple regression analysis. The results of the analysis show that the first hypothesis is firm size does not affect the profitability of the company. The second hypothesis is Cash Conversion Cycle effect on profitability.Keywords: Firm Size, Cash Conversion Cycle, and Profitability